A Note on Kaehlerian Manifolds with Vanishing Bochner Curvature Tensor - S.S. Pujar2, S. D. Devkhile1* (Recent Research in Science and Technology, 2011)
The purpose of the paper is to prove a theorem in a Kaehlerian manifold M with vanishing Bochner curvature tensor replacing the condition of constancy of scalar curvature and the length of the Ricci Tensor by the harmonic length of the Ricci tensor.